PENGEMBANGAN BAHAN AJAR IPS BERBASIS KERAGAMAN BUDAYA BATIK JENOGOROAN UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA - Hidayah, Siti Nurul (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2019)
AbstractThis study aims to improve critical thinking through the development of social sciencesteaching material toward cultural diversity batik jenogoroan in students class VII SMPN 2Bojonegoro. The research was conducted in three stages following the draft Borg and Gall, thatis the preliminary studies aimed, the stage of product designing teaching materials students withthe module, and continued with the testing stage or stages of implementation in the classroomdesign was one group pretest-posttest design. Data from the research results obtained asfollows: (1) the feasibility of module based cultural diversity batik jenogoroan worthy usedthrough 3 expert validation test, the feasibility of module seen from three components: content,presentation, and language. The results of the validation of third validator namely: the averagescore of the content component 3.53, 3.40 linguistic components, and presentation componentsof 3.55. All three scores indicate good category/feasible, which means module based culturaldiversity-based batik jenogoroan can be used with minimal revision. (2) the effectiveness ofmodule toward cultural diversity batik jenogoroan can enhance students' critical thinking can beseen from the test results between the pre-test and post-test, the results showed that the averagescore pre test 72.13%, while the average score of post test 80.35%. The results of the pre-test topost-tets increased 8.22. Based on the analysis, it can be concluded that based teachingmaterials cultural diversity batik jenogoroan can effectively improve critical thinking students'VII classes in social studies, especially on the matter of cultural diversity when seen from thetest results that have increased.Keywords: Teaching Materials, Cultural Diversity, Batik Jenogoroan, Critical Thinking